Avaliação do uso de Hymenaea stigonocarpa Mart. ex Hayne sobre a atividade adaptogênica e na expressão de biomarcadores do estresse oxidativo em cérebro de animais com estresse induzidos - Machado, Hélen Lara (2014)
Hymenaea stigonocarpa Mart. ex Hayne (Fabaceae) known as ―jatobá-do-cerrado‖ is a species native to the Brazilian savannah. The plant is popularly used as fortifier, aphrodisiac and brain stimulant. In this study, we show that Wistar rats treated with H. stigonocarpa for 14 days and subjected to chronic stress by restriction and cold for 7 days, decreased levels of corticosterone and normalized serum biochemical parameters. The treatment of H. stigonocarpa showed no toxicity, promoted an improved redox state in brain regions (cerebellum, cerebral cortex, striatum and hippocampus) and increased total antioxidant capacity, suggesting a potential adaptogenic and neuroprotective effect against stress-induced changes.